2019
DOI: 10.1177/0284185119847678
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain network centrality in patients with trigeminal neuralgia: a resting-state fMRI study

Abstract: Background Neuroimaging studies revealed that trigeminal neuralgia was related to alternations in brain anatomical function and regional function. However, the functional characteristics of network organization in the whole brain is unknown. Purpose The aim of the present study was to analyze potential functional network brain-activity changes and their relationships with clinical features in patients with trigeminal neuralgia via the voxel-wise degree centrality method. Material and Methods This study involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
19
1
1
Order By: Relevance
“…65,67 In addition to structural changes, fMRI studies demonstrated different patterns of brain activation in patients with TN when compared to healthy controls. 66,68,69,7476 A different pattern of activation was also observed in TN patients who report pain after stimulation of trigger zones versus patients who do not. 68 Patients with pain evoked by light tactile stimulation showed a bilateral activation of the primary and secondary somatosensory cortices, the ACC, and the prefrontal cortex, contralateral activation of insula and thalamus, ipsilateral activation of the medial cingulate cortex and spinal trigeminal nucleus, and activation of the medial brainstem, including the periaqueductal gray.…”
Section: Pathophysiology Of Classical Tnmentioning
confidence: 94%
“…65,67 In addition to structural changes, fMRI studies demonstrated different patterns of brain activation in patients with TN when compared to healthy controls. 66,68,69,7476 A different pattern of activation was also observed in TN patients who report pain after stimulation of trigger zones versus patients who do not. 68 Patients with pain evoked by light tactile stimulation showed a bilateral activation of the primary and secondary somatosensory cortices, the ACC, and the prefrontal cortex, contralateral activation of insula and thalamus, ipsilateral activation of the medial cingulate cortex and spinal trigeminal nucleus, and activation of the medial brainstem, including the periaqueductal gray.…”
Section: Pathophysiology Of Classical Tnmentioning
confidence: 94%
“…Previously, some rs-fMRI studies using graph theory have attempted to characterize the global brain modularity as well as key nodal features in CTN to elucidate the reorganization processes of brain networks [ 8 , 27 ]. Given that the FC between brain regions is constrained by the brain topological organization [ 28 ], aberrant dFNC pattern may be additionally accompanied by altered dynamic topological properties.…”
Section: Introductionmentioning
confidence: 99%
“…When the DON patient is examined, the functional state of the visual cortex and visual pathway can be noninvasively assessed. Therefore, resting fMRI has been successfully applied in the neurological studies of specific eye diseases (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%